Earnings quality: The Impact of implementation of IFRS-based financial accounting standard - Soegeng Soetedjo, Onong Junus,; Habiburrochman, H (Opción, 2019)
The study aims to investigate the impact of the implementation of the International Financial Report Standard (IFRS) based financial accounting standards using the Stubben model. Findings reveal that the implementation of IFRS-based Financial Accounting Standard can suppress or reduce the earnings management done by the company in which the lower earnings management decreases, the better the earnings quality. In conclusion, the number of companies carried out from the earning management decreases from 2010 to 2011, even though the level of decrease is not significant.